INO80 promotes H2A.Z occupancy to regulate cell fate transition in pluripotent stem cells. Issue 12 (17th June 2021) - Yu, Hongyao; Wang, Jiajia; Lackford, Brad; Bennett, Brian; Li, Jian-liang; Hu, Guang
Abstract: The INO80 chromatin remodeler is involved in many chromatin-dependent cellular functions. However, its role in pluripotency and cell fate transition is not fully defined. We examined the impact of Ino80 deletion in the naïve and primed pluripotent stem cells. We found that Ino80 deletion had minimal effect on self-renewal and gene expression in the naïve state, but led to cellular differentiation and de-repression of developmental genes in the transition toward and maintenance of the primed state. In the naïve state, INO80 pre-marked gene promoters that would adopt bivalent histone modifications by H3K4me3 and H3K27me3 upon transition into the primed state. In the primed state, in contrast to its known role in H2A.Z exchange, INO80 promoted H2A.Z occupancy at these bivalent promoters and facilitated H3K27me3 installation and maintenance as well as downstream gene repression. Together, our results identified an unexpected function of INO80 in H2A.Z deposition and gene regulation. We showed that INO80-dependent H2A.Z occupancy is a critical licensing step for the bivalent domains, and thereby uncovered an epigenetic mechanism by which chromatin remodeling, histone variant deposition and histone modification coordinately control cell fate. Graphical Abstract: